3D 프린팅 기술을 적용한 스플린트의 제작 용이성 향상을 위한 아래팔 기하 정보 비교에 관한 연구 - 장지홍(Ji Hong Chang) (한국정보전자통신기술학회 논문지, 2019)
A splint is one of assisting devices for the disabled with hemiplegia or contracture and is manually made by an experienced expert. Heated thermoplastic materials are continuously fitted to the affected part. This traditional method has a possible risk of low-temperature burn, quality variance of the splint due to the proficiency of maker. etc. While various approaches has been made using 3D printing technology in order to redeem those disadvantages, they still carry high cost issues with 3D scanners or accuracy issues with manual measurement. This research begins with symmetrical characteristics of human body and focuses on the preliminary study for the possibility of splint manufacturing with 3D printing technology based on geometric characteristics of unaffected arm. 3D right and left forearm models of healthy male adults were created by photogrammetry software and a series of digital images in order to measure the circumference and cross-sectional area of the forearm models at every 20mm from the elbow. The circumference and cross-sectional area showed tolerable levels of differences between both sides within subjects; The circumference and cross-sectional area showed very strong correlations between both sides within subjects. From these findings, the possibility of splint manufacturing with 3D printing technology could be confirmed based on the geometric characteristics of unaffected side. 스플린트는 마비, 구축 등이 나타난 환측에 적용하는 대표적인 보조기로서 전통적으로 숙련된 전문가의 수작업을 통해 제작된다. 제작과정은 열가소성 소재를 가열한 후 부드러워진 소재를 환측 부위에 접촉하며 해당 부위의 표면에 피팅시키는 과정을 반복하여 이루어진다. 이러한 전통적 방식은 저온화상의 위험, 제작자의 숙련도에 따른 완성도의 차이 등 여러 문제점을 가지고 있다. 이러한 단점을 보완하기 위하여 3D 프린팅 기술을 이용한 다양한 접근이 시도되고 있으나 3D 스캐너를 이용하는 경우 고비용의 문제, 수작업 측정의 경우 정확도의 문제 등의 단점을 나타내고 있다. 본 연구는 인체의 좌우 대칭성에 착안하여 건측 아래팔의 기하 특징을 이용하여 환측 스플린트를 3D 프린팅 기술로 제작하는 가능성에 관한 사전 연구이다. 디지털 사진과 사진측량기법을 이용하여 건강한 성인 남성으로부터 양측 아래팔의 3차원 가상 모델을 생성하고, 매 20mm 위치마다 둘레 길이 및 단면적을 측정하였다. 동일한 피험자네서 우세측과 비우세측 사이의 둘레 길이 및 단면적은 허용할 만한 수준의 차이를 나타냈으며, 우세측과 비우세측 사이에서 동일한 변수들 간에 높은 수준의 양의 상관관계를 나타냈다. 이러한 결과로부터 건측 아래팔의 기하 특징을 이용하여 3D 프린팅 기술의 적용을 통해 환측 스플린트 제작 가능성을 확인하였다.